Leveraging IsoArcH for isotope paleopathology: The example of the dataset from the Jedlička collection (Central Europe, 19th century CE) - Salesse, Kévin; Drtikolová Kaupová, Sylva; Kharobi, Arwa; Colombo, Antony; Brůžek, Jaroslav; Kuželka, Vítězslav; Velemínský, Petr (Data in brief, 2023)
The article introduces the enhancements made to the IsoArcH database for isotope paleopathology. This includes the addition of new metadata fields, which allow for describing abnormal anatomical or physiological conditions in humans and animals at either the individual or sample level. To showcase the novel features of the database, the article features a unique dataset of carbon and nitrogen isotope values obtained on bulk bone collagen from 42 clinically-documented cases of the Jedlička pathological-anatomical reference collection, dating from the 19th century CE and curated at the National Museum in Prague, Czechia. The dataset includes 70 combined isotopic measurements from individuals who underwent anatomizations between 1841 and 1900 and had distinct bone diseases/disorders: i.e. syphilis, rickets, osteosarcoma, osteomyelitis, and healed fractures. Finally, the article highlights the value of the data in helping the isotope bioarchaeology and paleopathology communities in their understanding of disease processes.
Keywords: Bone infection; Bone cancer; Stable isotope analysis; Carbon and nitrogen; Metabolic bone disease; Treponemal disease; Collagen; Bone trauma